VD_FINDINFO Jug / 2024 / 213 vom 5. Oktober 2023 - VD Tribunal cantonal (2023)
REJET DE LA DEMANDE, ACQUITTEMENT, LÉSION CORPORELLE GRAVE, CONTRAINTE SEXUELLE | 47 CO, 122 al. 2 CP, 189 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH), 9 CPP (CH)